2010
DOI: 10.1542/peds.2010-0420
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in End-of-Life Support in the Pediatric Intensive Care Unit

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Studies from the 1990s demonstrated limitation of end-of-life support in 30% to 58% of US PICU deaths. Little has been published from the United States since that time. More-recent publications from Australia showed limitation in 74% to 84% of deaths. WHAT THIS STUDY ADDS:The authors address a gap in the literature by describing recent end-of-life support practices in 30 PICUs across the United States. abstract OBJECTIVE: Our purpose was to examine alterations in end-of-life suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
4
31
1
Order By: Relevance
“…34,35 Death in the PICU continues to be common in children after withdrawal of technological support. 38 Whether the involvement of a PPC team leads to earlier limits on resuscitative efforts Technology-based decision aids (eg, videos, apps) for parents and pediatric patients How and where patients die PPC teams help shift the location of death away from PICU and inpatient settings to home and hospice settings. 37,39,41,62 Identification and clarification of factors that influence the preferred location of death Building a better healthcare system Barriers to palliative care Uncertain patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 Death in the PICU continues to be common in children after withdrawal of technological support. 38 Whether the involvement of a PPC team leads to earlier limits on resuscitative efforts Technology-based decision aids (eg, videos, apps) for parents and pediatric patients How and where patients die PPC teams help shift the location of death away from PICU and inpatient settings to home and hospice settings. 37,39,41,62 Identification and clarification of factors that influence the preferred location of death Building a better healthcare system Barriers to palliative care Uncertain patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…37 Nonetheless, children with advanced heart, lung, immune, and infectious diseases continue to die in the PICU after receiving highly technical medical support at the end of life and after the withdrawal of life-sustaining interventions. 33,36,38 Patients and families vary in terms of preference for location of end-of-life care, 39 and the majority of children die in a hospital setting. 40 This can actively change to home deaths with PPC involvement.…”
Section: How and Where Patients Diementioning
confidence: 99%
“…7,8 Research from Australia, 4,5,9 the United States, 10,11 and the United Kingdom 1 has found that children most frequently die as a result of withdrawal of life support, whereas studies from Brazil, 3 France, and Eastern and Central Europe 2 identify that most children die in PICUs as a result of failed cardiopulmonary resuscitation. Some have argued that this can be attributed largely to cultural differences related to end-oflife care practices and the social acceptance of the death of a child.…”
mentioning
confidence: 99%
“…Brain death is a distinct mode of death both in adult and pediatric population; it is estimated that BD accounts for approximately 16-23% of deaths in the pediatric intensive care unit (PICU), while the corresponding values for adults are quite similar and depending on the nature of the unit, rising from 15% in multidisciplinary units up to 30% in neurocritical units [3][4][5][6]. Most research about BD involves adults; however, not all principles regarding BD could be transferred to children.…”
Section: Introductionmentioning
confidence: 99%